Monetary policy rules - George T. McCandless (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2021)
Most models of monetary policy specify a single rule (frequently a Taylor rule) for setting a policy interest rate based on monetary aggregates. Here I consider an economy where the government has two channels for injecting or withdrawing money from the economy: a policy of monetary transfers to or taxes from households handled by the fiscal authorities and another for injecting or withdrawing money from the financial system handled by the monetary authorities. Since the two channels produce different responses in the economy, this paper studies how different combinations of these policies with the same aggregate money growth give different macroeconomic results. This is an important issue because central banks are often called upon to use their interest rate channel to sterilize monetary shocks under an at least implicit assumption that this will neutralize the shocks. In addition, by having two types of households, skilled and unskilled, with different savings opportunities, it is possible to study the disparate effects of different mixtures of the two channels on richer and poorer households as well as the effect on aggregate output and inflation. Results are that the utility of the unskilled is higher the higher the transfer rates and that of the skilled is lower. In general, at given transfer rates, the unskilled prefer higher inflation rates and the skilled lower. At higher positive rates of transfer to the unskilled both the unskilled and the skilled prefer higher inflation rates. This suggests that in countries where unskilled are the majority, transfers to the unskilled are likely to be a social choice outcome even at the cost of reduced total output. The paper also points out that concentrating on aggregate output and inflation as policy objectives can be problematic.
Keywords: 330